PENINGKATAN KETERAMPILAN MENULIS TEKS NARASI MELALUI PICTURE WORD INDUCTIVE MODEL PADA SISWA KELAS IV SDN MENTENG ATAS 14: Penelitian Tindakan Kelas - Firdha Zahrah; Juhana Sakmal; Uswatun Hasanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to improve narrative text writing skills through the Picture Word Inductive Model (PWIM) for fourth-grade students at SDN Menteng Atas 14. This classroom action research follows the Kemmis and McTaggart model, conducted in two cycles. Each cycle consists of four stages: planning, acting, observing, and reflecting. The subjects of this study were 22 students of class IV-A at SDN Menteng Atas 14. The research was conducted during the even semester of the 2025/2026 academic year. Data were collected through tests, observations, field notes, and documentation. The results indicated an improvement in students' narrative text writing skills. In cycle I, 15 students achieved a score of ≥75, with a percentage of 68.18%. In cycle II, 20 students achieved a score of ≥75, reaching a percentage of 90.90%. Teacher activity in cycle I reached 82%, while student activity reached 79%. In cycle II, teacher activity increased to 100%, and student activity rose to 97%. Based on these findings, it can be concluded that the application of PWIM can effectively improve students' narrative text writing skills.